Comparative effects of topical Maresin-1 and cyclosporine A in a capsaicin-induced rat model of neurotrophic keratopathy - Sezis, Selen Canan; Kobat, Sabiha Gungor; Kuloglu, Tuncay; Ilhan, Nevin; Erten, Fusun (Academic Press Ltd- Elsevier Science Ltd, 2026)
Purpose: To evaluate and compare the effects of topical Maresin-1 (MaR1) and cyclosporine A (CsA) in a capsaicin-induced rat model of neurotrophic keratopathy (NK). Methods: A total of 40 Sprague-Dawley rats were allocated to five groups (n = 8 per group): Control, NK, NK + Vehicle, NK + CsA (0.05%), and NK + MaR1. Except for the Control group, all animals received a single subcutaneous injection of capsaicin (50 mg/kg) on postnatal day 2. Topical treatments were applied twice daily for 14 days. Corneal TrkA, TNF-alpha, and Caspase-3 expression were assessed by immunohistochemistry and Western blot. Results: Both treatment groups significantly restored TrkA expression and reduced TNF-alpha and Caspase-3 relative to NK + Vehicle (p < 0.05 for all). CsA produced greater suppression of TNF-alpha than MaR1 (p < 0.001), whereas MaR1 demonstrated greater reduction in Caspase-3 than CsA (p = 0.013), with no significant difference between groups for TrkA (p = 0.054). Conclusion: Both MaR1 and CsA significantly attenuated the neurotrophic, inflammatory, and apoptotic changes associated with experimental NK. The distinct efficacy profiles of the two agents suggest complementary mechanisms of action and warrant further investigation of MaR1 in neurotrophic keratopathy.
Keywords: Tissue Regeneration; Current Challenges; Corneal; Expression; Mediator; Death; Cells